Pengaruh Kesadaran Wajib Pajak dan Tingkat Pendapatan terhadap Kepatuhan Pembayaran Pajak Kendaraan Bermotor di Kabupaten Tanah Datar - Tisti Amanda; Deviani Deviani (Universitas Negeri Padang, 2026)
The purpose of this study was to determine the effect of taxpayer awareness and income level on motor vehicle tax payment compliance in Tanah Datar Regency. This research used a quantitative approach by distributing questionnaires to 400 respondents who are registered motor vehicle taxpayers. The sampling technique used was incidental sampling. The results of the partial test showed that taxpayer awareness had a positive and significant effect on tax payment compliance, with a significance value of <0.001. Likewise, income level had a positive and significant effect with a significance value of <0.001. Simultaneously, both variables had a significant influence on motor vehicle tax payment compliance. These findings support the internal attribution theory, which suggest that individual awareness is key to encouraging compliance. Recommendations for further research include examining additional factors such as tax sanctions or service quality and applying broader sampling methods to enhance generalizability.